Salt to the sea : a novel - Sepetys, Ruta (2016)
"As World War II draws to a close, refugees try to escape the war's final dangers, only to find themselves aboard a ship with a target on its hull"--
Library Journal
Booklist
School Library Journal
Publishers Weekly
12-19.
7-12.
Keywords: World War, 1939-1945 -- Juvenile fiction